Análisis diagnóstico de los valores turísticos industriales del proyecto hidroeléctrico coca codo Sinclair, napo - sucumbíos - Sotomayor Amaiquema, Roberto Luis (2016)
The research carried out on Analysis diagnosis of the industrial tourism values of Proyecto Hidroeléctrico Coca Codo Sinclair, Napo - Sucumbíos was in scientific bibliographical means and on-site visits, using tools such as visitor surveys and interviews with Coca Codo Sinclair Ing. Gonzales, which allowed to obtain real and current data, and thus to make the approach of the problem and the possible solutions, in a respective way the suggested proposal. With the proposed proposal to carry out an analysis diagnosis of the industrial tourist values of Proyecto Hidroeléctrico Coca Codo Sinclair, Napo - Sucumbíos, it`s possible to use the local resources as tourist potential to possess Ecuador as a pioneer in the design of industrial tourism As have been countries like Spain in other typologies. The report intends to be part of a scientific study aimed at national tourism development and that Ecuador not only has a category 5 destination but is at the forefront of global tourism as a successful model of resource use for multiple economies such as Energy and tourism. It has the respective conclusions as analysis of the study and the recommendations as strategies that will serve for the accomplishment by which the present study was carried out, this with the support of the respective theoretical foundation of scientific books that helped to corroborate the lived experience By the respondents.